Réponses

2014-02-05T23:45:12+01:00
Exercice 4
1.a. x+y = 3 donc x=3-y
on remplace dans la 2ème équation :
x - y = 1
3-y -y = 1
-2y = 1-3
-2y = -2
2y = 2
y = 2/2
y = 1
x = 3-y = 3-1
x = 2

b.x-2y = 3 donc x = 2y+3
on remplace dans la 2ème équation :
2x - y = 1
2(2y+3) - y = 1
4y+6-y = 1
3y = 1-6
3y = -5
y = -5/3

x = 2y+3 = 2*-5/3 + 3 = -10/3 + 9/3 (* signifie multiplié par)
x = -1/3

c. x-3y = 5 donc x = 5+3y
on remplace dans la 2ème équation :
3x - y = 5
3(5+3y) - y = 5
15+9y-y = 5
8y = 5-15
8y = -10
y = -10/8
y = -5/4

x = 5+3y
x = 5+3*-5/4 = 20/4 -15/4
x = 5/4

2. a. x+y = 3 donc y = 3-x
on remplace dans la 2ème équation :
x - y = 1
x -(3-x)= 1
x-3+x = 1
2x = 1+3
2x = 4
x = 4/2
x = 2

y = 3-x
y = 3-2
y = 1

b. 2x-y = 4 donc 2x-4 = y
on remplace dans la 2ème équation :
x - 4y = 2
x -4(2x-4) = 2
x -8x + 16 = 2
-7x = 2-16
-7x = -14
x = 14/7
x = 2

y = 2x-4
y = 2*2 -4
y = 4 -4
y = 0

c. 3x + 2y = 1 donc y = (1-3x)/2
on remplace dans la 2ème équation :
x-2y = 3
x-2(1-3x)/2 = 3
x-1+3x = 3
4x = 3+1
4x = 4
x = 4/4
x = 1

y = (1-3x)/2
y = (1-3)/2
y = -2/2
y = -1

3. a. x+y = 5 donc x =  5-y
on remplace dans la 2ème équation :
x - y = 1
5-y-y = 1
-2y = 1-5
-2y = -4
y = 4/2
y = 2

x = 5-y
x = 5 - 2
x = 3

b. 3x + 4y = 24 donc x = (24-4y)/3 = 8 -4y/3
on remplace dans la 2ème équation :
x + 5 y = 19
8 -4y/3 + 5y = 19
-4y/3 + 15y/3 = 19-8
11y/3 = 11
11y = 11*3
y = 3*11/11
y = 3

x = 8 -4y/3
x = 8-4*3/3
x = 8-4
x = 4

c. 2x - y = 4 donc -y = 4-2x d'où y = 2x-4
on remplace dans la 2ème équation :
5x - y = 1
5x+4-2x = 1
3x = 1-4
x = -3/3
x = -1

y = 2x-4
y = 2*-1 -4
y = -2-4
y = -6